Dust core, alloy particles, electronic component, electronic device, motor, and generator

By using the solid solution cover layer of Fe2SiO4 or Fe2SiO4 and Mg2SiO4 and low-silicon concentration metal particles in the alloy particles of the powdered magnetic core, the problems of insufficient eddy current loss, strength and relative permeability in the prior art are solved, and a high-performance powdered magnetic core is realized.

CN119631149APending Publication Date: 2025-03-14NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056081.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-11
Filing Date
2023-08-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While reducing eddy current losses, the existing powdered magnetic cores have insufficient strength and relative magnetic permeability, making it difficult to meet high performance requirements.

Method used

A core formed of iron and silicon alloys is used, and a solid solution containing Fe2SiO4 or Fe2SiO4 and Mg2SiO4 in its cover part, and metal particles with low silicon concentration are spread around the outer periphery, thereby enhancing magnetic connection through the clamping structure.

Benefits of technology

It realizes a powdered magnetic core with small eddy current loss, high strength and high relative magnetic permeability, which is suitable for high-frequency and high-performance electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631149A_ABST
    Figure CN119631149A_ABST
Patent Text Reader

Abstract

Provided is a dust core having low eddy current loss, high strength, and high relative permeability. The powder magnetic core (1) includes a plurality of alloy particles (3), and each alloy particle (3) includes a core portion (5) formed of an alloy containing iron and silicon and a covering portion (7) covering the core portion (5). The covering part (7) contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4. A plurality of metal particles (9) are arranged on the outer peripheral edge of the covering part (7) in a dispersed manner, and the metal particles (9) contain silicon at a proportion less than that of the alloy of the core part (5). At least some of the metal particles (9) exist between adjacent alloy particles (3) so as to be sandwiched by the covering sections (7).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a powder magnetic core, alloy particles, electronic components, electronic devices, motors, and generators. Background Art

[0002] The powder magnetic core disclosed in Patent Document 1 includes soft magnetic particles containing Fe and a coating layer covering the soft magnetic particles. The compound layer included in the coating layer is formed by reacting a silicone resin with ferrite.

[0003] In the soft magnetic material disclosed in Patent Document 2, Fe and O diffused into the soft magnetic metal particles during sintering react with the added element M to form Fe-O compounds and Fe-MO compounds. During cooling, a eutectic phase transition from the FeO phase to the Fe3O4 phase and the Fe phase occurs.

[0004] The soft magnetic material disclosed in Patent Document 3 has a structure in which silicon in a silicon dispersion layer reacts with soft magnetic ferrite during sintering to form Fe2SiO4 or the like on the surface of iron-based soft magnetic base material particles.

[0005] The magnetic material disclosed in Patent Document 4 has a multilayer structure including an oxide layer containing Fe and O and amorphous SiO 2. It has a structure in which Fe 2 SiO 4 and the like are precipitated in amorphous SiO 2 .

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-75566

[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-60183

[0010] Patent Document 3: Japanese Patent Application Publication No. 2016-86124

[0011] Patent Document 4: Japanese Patent Application Publication No. 2019-09307 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] Since the powder magnetic core disclosed in Patent Document 1 uses silicone resin to form the compound layer contained in the cover layer, the reduction of eddy current loss is insufficient, and the strength and relative magnetic permeability are also low.

[0014] Since the soft magnetic material disclosed in Patent Document 2 uses a method of causing a FeO phase eutectoid transformation, the reduction of eddy current loss is insufficient, and the strength and relative magnetic permeability are also low.

[0015] Since the soft magnetic material disclosed in Patent Document 3 uses silicon particles in the process of forming Fe2SiO4 and the like, the structure tends to become non-uniform, the reduction of eddy current loss is insufficient, and the strength and relative magnetic permeability also become low.

[0016] Since the magnetic material disclosed in Patent Document 4 contains amorphous SiO 2 , the relative magnetic permeability becomes low.

[0017] Therefore, a powder magnetic core with small eddy current loss, high strength and high relative magnetic permeability is needed.

[0018] The present disclosure is made in view of the above actual situation, and its purpose is to provide a powder magnetic core with small eddy current loss, high strength and high relative magnetic permeability. The present disclosure can be implemented in the following ways.

[0019] Solutions for solving problems

[0020] [1] A powder magnetic core comprising a plurality of alloy particles,

[0021] The alloy particles have:

[0022] a core formed of an alloy comprising iron and silicon; and

[0023] a covering portion covering the core portion,

[0024] The covering portion contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4,

[0025] A plurality of metal particles are disposed in a dispersed manner on the outer periphery of the cover portion, wherein the metal particles contain silicon at a lower ratio than the alloy.

[0026] At least a portion of the metal particles is present between adjacent alloy particles in a form of being sandwiched by the covering portion.

[0027] [2] An alloy particle comprising:

[0028] a core formed of an alloy comprising iron and silicon; and

[0029] a covering portion covering the core portion,

[0030] The covering portion contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4,

[0031] A plurality of metal particles are disposed in a dispersed manner on the outer periphery of the coating portion, and the metal particles contain silicon at a lower ratio than that of the alloy.

[0032] [3] The powder magnetic core according to [1], wherein:

[0033] The covering portion contains a solid solution of Fe2SiO4 and Mg2SiO4,

[0034] The solid solution has an olivine-type structure.

[0035] [4] The powder magnetic core according to [1] or [3], wherein:

[0036] The core has the following composition:

[0037] Contains by mass%

[0038] Silicon (Si): 2% or more and 10% or less,

[0039] Aluminum (Al): 0% or more and 10% or less,

[0040] Chromium (Cr): 0% to 20% inclusive, with the remainder being iron and inevitable impurities.

[0041] [5] The powder magnetic core according to [4], wherein the component composition is a composition that does not cause an A3 phase transition from an α phase to a γ phase at a temperature of 800° C. to 1200° C.

[0042] [6] The alloy particles according to [2], wherein:

[0043] The covering portion contains a solid solution of Fe2SiO4 and Mg2SiO4,

[0044] The solid solution has an olivine-type structure.

[0045] [7] The alloy particles according to [2] or [6], wherein:

[0046] The core has the following composition:

[0047] Contains by mass%

[0048] Silicon (Si): 2% or more and 10% or less,

[0049] Aluminum (Al): 0% or more and 10% or less,

[0050] Chromium (Cr): 0% to 20% inclusive, with the remainder being iron and inevitable impurities.

[0051] [8] The alloy particles according to [7], wherein the component composition is a composition that does not cause an A3 phase transformation from an α phase to a γ phase at a temperature of 800° C. to 1200° C.

[0052] [9] An electronic component comprising the powder magnetic core according to any one of [1] and [3] to [5].

[0053]

[10] The electronic component according to [9], comprising the powder magnetic core and a coil.

[0054]

[11] An electronic device comprising the electronic component described in [9] or

[10] .

[0055]

[12] An electric motor comprising the powder magnetic core according to any one of [1] and [3] to [5].

[0056]

[13] A generator comprising the powder magnetic core according to any one of [1] and [3] to [5].

[0057] Effects of the Invention

[0058] The powder magnetic core disclosed in the present invention can provide a powder magnetic core with small eddy current loss, high strength and high relative magnetic permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 A cross-sectional SEM image of the powder magnetic core is shown when the cross-sectional structure is observed.

[0060] Figure 2 Shown by Figure 1 Cross-sectional SEM image when observing with a narrow field of view.

[0061] Figure 3 This is an explanatory diagram schematically showing a cross-sectional SEM image when observing in a field of view in which a specific alloy particle and a part of the surrounding alloy particles are visible in the cross-sectional structure of the powder magnetic core.

[0062] Figure 4 This is a schematic diagram of an inductor using a powder magnetic core.

[0063] Figure 5 This is a schematic diagram of an inductor using a powder magnetic core.

[0064] Figure 6 This is a schematic diagram of an inductor using a powder magnetic core.

[0065] Figure 7 This is a schematic diagram of a noise filter using a powder magnetic core.

[0066] Figure 8 This is a schematic diagram of a reactor using a powder magnetic core.

[0067] Fig. 9 This is a schematic diagram of a transformer using a powder core.

[0068] Fig.10 This is a circuit diagram of a noise filter using a powder magnetic core.

[0069] Fig.11This is a schematic diagram of a motor using a powder core.

[0070] Fig.12 This is a schematic diagram of a generator using a powder magnetic core. DETAILED DESCRIPTION

[0071] The present disclosure is described in detail below. It should be noted that, in this specification, unless otherwise specified, the description using "to" for a numerical range includes a lower limit and an upper limit. For example, the description of "10 to 20" includes "10" as a lower limit and includes "20" as an upper limit. That is, "10 to 20" has the same meaning as "10 or more and 20 or less". In addition, in this specification, the upper limit and lower limit of each numerical range can be arbitrarily combined.

[0072] 1. Structure of pressed powder core

[0073] like Figure 1 As shown in the cross-sectional SEM image of FIG. 1 , the powder magnetic core 1 has a plurality of alloy particles 3. Figure 2 As shown in the cross-sectional SEM image of , alloy particle 3 includes a core portion 5 and a covering portion 7 covering the core portion 5 . Figure 2 It is compared Figure 1 The cross-sectional SEM image when observed with a narrow field of view. The core 5 is formed of an alloy containing iron (Fe) and silicon (Si). The covering portion 7 contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4. A plurality of metal particles 9 are arranged in a dispersed manner on the outer periphery of the covering portion 7. It should be noted that the shape of the powder core 1 is not particularly limited. In addition, Figure 1 , Figure 2 A cross-sectional SEM image is shown when the covering portion contains Fe2SiO4.

[0074] The core 5 is a soft magnetic metal particle containing iron and silicon. The core 5 may contain aluminum (Al), chromium (Cr), etc. The core 5 contains, for example, 1 mass % to 10 mass % silicon, 10 mass % or less aluminum, 20 mass % or less chromium (Cr), and the remainder is iron and inevitable impurities.

[0075] From the perspective of increasing the saturation magnetic flux density of the powder magnetic core 1, the core 5 preferably has the following composition: in terms of mass %, silicon (Si): 2% to 10%, aluminum (Al): 0% to 10%, chromium (Cr): 0% to 20%, and the remainder is iron and inevitable impurities. The aluminum (Al) contained in the core 5 may be 0% by mass. The chromium (Cr) contained in the core 5 may be 0% by mass.

[0076] The composition of the core 5 is preferably a composition that does not undergo an A3 phase transition from the α phase to the γ phase at a temperature of 800°C or more and 1200°C or less. The A3 phase transition from the α phase to the γ phase is, for example, a phase transition from a body-centered cubic lattice (BCC) phase to a face-centered cubic lattice (FCC) phase. As a result, it is difficult for micro cracks to be generated in the cover 7, and it is possible to suppress sintering between adjacent alloy particles 3 through cracks, thereby suppressing the reduction of insulation, and further suppressing the reduction of eddy current loss.

[0077] The average particle size of the core 5 is greater than 10 μm and less than 70 μm, preferably greater than 10 μm and less than 50 μm, and more preferably greater than 10 μm and less than 40 μm. The average particle size of the core 5 can be appropriately changed according to the frequency band in which the powder core 1 is used. For example, when it is assumed to be used in a high frequency band exceeding 50 kHz, it is preferably greater than 10 μm and less than 50 μm. When the powder core 1 is used in a high frequency band, eddy currents are generated in the core 5, which may cause losses (eddy current losses). Since the amount of eddy current loss generated is proportional to the square of the frequency and proportional to the square of the particle size, when used in a high frequency band, a smaller particle size is preferred.

[0078] Regarding the average particle size of the core 5, the area equivalent circle diameter is calculated based on the particle area obtained by observing the cross section of the compressed magnetic core 1 using FE-SEM (field emission scanning electron microscope), and this is used as the average particle size. Specifically, the average circle equivalent diameter is calculated as follows. In a specified observation field of view (for example, 200μm×200μm), focus on multiple cores 5 that can be observed without defects. Calculate the diameter (area equivalent circle diameter) of an ideal circle (true circle) having an area equal to the area (projected area) of each particle image of the core 5 as the circle equivalent diameter of each particle. Then, the circle equivalent diameters of each particle are arithmetic averaged to obtain the average circle equivalent diameter. The circle equivalent diameter of each particle and the average circle equivalent diameter can be calculated using conventional image analysis software.

[0079] The covering portion 7 contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4. The crystalline phase (Fe2SiO4, MgFeSiO4, etc.) in the covering portion 7 is identified by performing XRD (X-ray diffraction) analysis on the cross section of the pressed powder core 1. When the covering portion contains Fe2SiO4, it can be seen from the simple quantitative analysis of the composition ratio of each component using the reference intensity ratio (RIR) method that the amount of Fe2SiO4 in the covering portion 7 is the largest in the pressed powder core 1 except for the crystalline phase of the core 5. The average thickness of the covering portion 7 is greater than 0.01μm and less than 1μm. In addition, the thickness of the covering portion 7 is preferably greater than 0.015% and less than 10% of the average particle size of the core 5.

[0080] When the covering portion 7 contains a solid solution of Fe2SiO4 and Mg2SiO4, the composition formula of the solid solution can be expressed as: Mg X Fe 2―X Represented by SiO4. Here, X preferably satisfies the relationship of 0<X<2, more preferably satisfies the relationship of 0<X<1.2, and further preferably satisfies the relationship of 0.2<X<1.2. When the covering portion 7 contains a solid solution of Fe2SiO4 and Mg2SiO4, the solid solution is preferably formed with an arbitrary composition ratio of Fe2SiO4 and Mg2SiO4. When the covering portion 7 contains a solid solution of Fe2SiO4 and Mg2SiO4, the crystal structure of the solid solution detected by XRD (X-ray diffraction) analysis preferably has an olivine-type structure of the orthorhombic space group Pbnm. Thereby, the thermal expansion coefficient of the covering portion 7 can be made close to the thermal expansion coefficient of the alloy of the core portion 5, and during the annealing process, the covering portion 7 is not prone to cracking, and the reduction of eddy current loss can be suppressed.

[0081] The metal particles 9 are particles with a low silicon concentration. The metal particles 9 contain silicon at a lower ratio than the alloy 5. The silicon concentration in the metal particles 9 can be measured by performing SEM-EDS (energy dispersive X-ray analysis) on the cross section of the pressed powder core 1. The metal particles 9 are preferably pure iron. The average particle size of the metal particles 9 is, for example, greater than 0.1 μm and less than 3 μm. The ratio of the average particle size of the metal particles 9 to the average particle size of the alloy particles 3 is greater than 0.14% and less than 25%. A plurality of metal particles 9 are arranged in a dispersed manner on the outer periphery of the covering portion 7. Arranging a plurality of metal particles 9 in a dispersed manner means that two or more metal particles 9 are arranged in a spaced manner. It should be noted that in the cross-sectional image, it is preferred that two or more metal particles 9 are arranged on the outer periphery of one alloy particle 3, and it is more preferred that three or more metal particles 9 are arranged on the outer periphery of one alloy particle 3. In addition, it is preferred that less than 50 metal particles 9 are arranged on the outer periphery of one alloy particle 3. It should be noted that it is preferred that parts of two or more metal particles 9 are sandwiched between adjacent alloy particles 3 .

[0082] At least a portion of the plurality of metal particles 9 is present between adjacent alloy particles 3 in the form of being sandwiched by the covering portion 7. It should be noted that all of the plurality of metal particles 9 may also be present between adjacent alloy particles 3 in the form of being sandwiched by the covering portion 7. In addition, a portion of the metal particles 9 may also be connected to the core portion 5. In addition, there may be gaps between the metal particles 9 and the adjacent alloy particles 3.

[0083] Reference Figure 3 , the configuration of the metal particles 9 will be described. Figure 31 is an explanatory diagram schematically showing a cross-sectional SEM image of a powder magnetic core when observed in a field of view in which a specific alloy particle 3 and a portion of the alloy particle 3 around it can be seen. Figure 3 When the alloy particle 3 (referred to as alloy particle 3A) at the center of the alloy particle 3 is formed, the first portion L1 ( Figure 3 The bold part in the figure) and the second part L2 ( Figure 3 The first portion L1 is a portion that is 1 μm or more away from the outer periphery of the metal particle 9. Figure 3 , a virtual circle C is drawn indicating a position 1 μm from the outer periphery of the metal particle 9. The portion of the contour L outside the virtual circle C is the first portion L1. The second portion L2 is the portion within 1 μm from the outer periphery of the metal particle 9. The portion of the contour L inside the virtual circle C is the second portion L2.

[0084] The length of the first portion L1 accounts for more than 50% of the length of the circumferential direction of the profile L. The length of the first portion L1 here refers to the total length of all the first portions L1 when there are multiple first portions L1 in the profile L. In addition, when focusing on the second portion L2, the length of the second portion L2 accounts for less than 50% of the length of the entire circumferential direction of the profile L. The length of the second portion L2 here refers to the total length of all the second portions L2 when there are multiple second portions L2 in the profile L.

[0085] A plurality of metal particles 9 ( Figure 3 9 in ). Figure 3 In the embodiment, alloy particles 3A and 3B are adjacent to each other, and alloy particles 3A, 3B, 3C, and 3D are present. At least a portion of the metal particles 9 ( Figure 3 In the figure, five metal particles 9A to 9E are present between adjacent alloy particles 3 in the form of being sandwiched by the covering portion 7. For example, metal particles 9A and 9B are present between alloy particles 3A and 3B in the form of being sandwiched by the covering portion 7. Metal particle 9C is present between alloy particle 3A and alloy particle 3C in the form of being sandwiched by the covering portion 7. Metal particles 9D and 9E are present between alloy particle 3A and alloy particle 3D in the form of being sandwiched by the covering portion 7.

[0086] 2. Effect of pressed powder core

[0087] In the powder magnetic core 1 of the present disclosure, Fe 2 SiO 4 or a solid solution of Fe 2 SiO 4 and Mg 2 SiO 4 is contained in the coating 7 , so the insulation between the alloy particles 3 is improved, and the eddy current loss can be reduced.

[0088] In the powder magnetic core 1 of the present disclosure, the melting point (1205° C.) of Fe 2 SiO 4 contained in the covering portion 7 is lower than the melting point (1371° C.) of iron oxide, so the covering portions 7 are easily sintered to each other, and the strength can be improved.

[0089] In the dust core 1 of the present disclosure, a plurality of metal particles 9 are arranged in a dispersed manner on the outer periphery of the cover 7, and the metal particles 9 contain silicon at a ratio less than that of the alloy of the core 5. At least a portion of the metal particles 9 is present between adjacent alloy particles 3 in the form of being sandwiched by the cover 7. Therefore, the relative magnetic permeability of the dust core 1 can be improved. In particular, the lower the silicon concentration of the core 5, the higher the relative magnetic permeability of the dust core 1 can be.

[0090] The powder magnetic core 1 of the present disclosure is formed by pressing raw material powder including alloy particles 3, so the strength can be improved. The coating 7 has a low silicon concentration and is deformed during pressing, so that the alloy particles 3 are easily bonded to each other.

[0091] In the compressed powder core 1 disclosed in the present invention, since a plurality of metal particles 9 are arranged in a dispersed manner on the outer periphery of the covering portion 7, and the metal particles 9 contain silicon in a smaller proportion than the alloy of the core portion 5, it is less likely to become a path for eddy currents compared to a structure in which the metal particles 9 are connected, thereby being able to reduce eddy current losses.

[0092] In the powder magnetic core 1 disclosed in the present invention, the covering portion 7 preferably contains a solid solution of Fe2SiO4 and Mg2SiO4, and the solid solution of Fe2SiO4 and Mg2SiO4 has an olivine structure. The thermal expansion coefficient of Mg2SiO4 is greater than the thermal expansion coefficient of Fe2SiO4, and is closer to the thermal expansion coefficient of the alloy of the core 5. The crystal structures of Mg2SiO4 and Fe2SiO4 are the same olivine structure, and a solid solution is formed at an arbitrary ratio. The larger the ratio of Mg2SiO4, the larger the thermal expansion coefficient of the solid solution. Therefore, by making the covering portion 7 contain a solid solution of Fe2SiO4 and Mg2SiO4, the thermal expansion coefficients of the covering portion 7 and the core portion 5 become close. For example, even during the annealing process, the covering portion 7 is not easy to crack due to the difference in thermal expansion coefficients between the two. As a result, eddy current loss can be suppressed.

[0093] In the powder magnetic core 1 disclosed in the present invention, the composition of the core 5 is preferably a composition that does not undergo an A3 phase transition from the α phase to the γ phase at a temperature of 800°C or more and 1200°C or less. When it is pure iron, for example, when gradually heated, an A3 phase transition from the α phase to the γ phase occurs at the A3 phase transition point of 911°C, resulting in a rapid volume contraction of more than 5%. On the contrary, when the pure iron is gradually cooled, the volume expands rapidly. When this phase transition occurs during annealing, tiny cracks will be generated in the covering portion 7, and sintering will be caused between adjacent alloy particles 3 through the cracks, the insulation will decrease, and it will be difficult to suppress eddy current losses. Even if the core 5 is an Fe-Si alloy, this phase transition may occur in a composition with a small amount of Si added. If the amount of Si, Al, Cr, etc. added to the core 5 is gradually increased, an alloy in which this phase transition does not occur can be formed. For example, when the core 5 is an Fe-Si alloy, it is preferably composed of 2% by mass or more and 10% by mass or less of Si. When the core 5 is a Fe-Al alloy, it preferably contains 1 mass % or more and 10 mass % or less of Al. When the core 5 is a Fe-Cr alloy, it preferably contains 13 mass % or more and 20 mass % or less of Cr. In the core 5, only Si may be added, but by adding Al and Cr at the same time, the amount of Si added can be reduced.

[0094] 3. Manufacturing method of pressed powder core

[0095] The method for producing the powder magnetic core 1 is not particularly limited. The production method will be described below.

[0096] (1) Preparation of coating powder

[0097] A ferrite coating is formed on the core 5 by plating. The coating can be formed by grinding, spraying, sol-gel, coprecipitation, etc. in addition to plating. Ferrite can be Ni ferrite, Zn ferrite, Mn ferrite, Mg ferrite, MnZn ferrite, NiZn ferrite, etc. in addition to the magnet Fe3O4.

[0098] In the plating method, an oxidizing agent (nitrite) is added to an aqueous solution containing the core 5 and divalent ions such as iron ions while controlling the pH to form a ferrite coating layer. The prepared aqueous solution is filtered and dried to obtain a coating powder.

[0099] (2) Heat treatment

[0100] The obtained coated powder is heat treated to obtain alloy powder including alloy particles 3. The core 5 is covered by a coating 7 containing a solid solution of Fe2SiO4 or Fe2SiO4 and Mg2SiO4. A plurality of metal particles 9 are dispersed around the outer periphery of the coating 7, and the metal particles 9 contain silicon at a lower ratio than the core 5.

[0101] (3) Molding (press molding)

[0102] The obtained alloy powder is pressed and annealed to obtain a powder core 1. The pressing is performed by applying a surface pressure of 0.5 GPa to 2.0 GPa, for example. In order to improve the formability, a small amount of an organic binder or an internal lubricant (such as stearate) may be mixed. In addition, a release agent such as stearate may be applied to the mold. In addition to uniaxial press molding, CIP (cold isostatic pressing) molding may also be performed.

[0103] It should be noted that the powder magnetic core 1 can also be obtained by press-molding and annealing the coated powder obtained in the above (1) without performing heat treatment.

[0104] (4) About heat treatment and annealing

[0105] During the annealing process, the ferrite coating reacts with silicon in the core 5 to form Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4. At the same time, during the annealing process, metal particles 9 with a low silicon concentration precipitate on the surface of the coating and become dispersed on the surface.

[0106] The heat treatment of the coated powder and the annealing after molding are carried out in a non-oxidizing atmosphere (N2 atmosphere, Ar atmosphere or H2 atmosphere). The maximum temperature of the heat treatment and annealing is preferably 700°C to 1050°C. This is because the formation reaction of the solid solution of Fe2SiO4 or Fe2SiO4 and Mg2SiO4 is accelerated, which can reduce eddy current loss. The maximum temperature of the heat treatment and annealing is more preferably 900°C to 1050°C. This is because the strain in the core 5 becomes smaller, which can reduce hysteresis loss. By making the maximum temperature of the heat treatment and annealing below 1050°C, the sintering of the alloy particles 3 can be suppressed, and the eddy current loss can be reduced. The annealing temperature is preferably maintained for more than 1 hour. This is because the formation reaction of the solid solution of Fe2SiO4 or Fe2SiO4 and Mg2SiO4 is accelerated, which can reduce eddy current loss. In the process of cooling from 600°C to 300°C, it is preferably cooled at a cooling rate of more than 2°C / min. This is to suppress the increase in eddy current loss caused by the eutectoid phase transformation of FeO when a trace amount of FeO is dissolved in Fe2SiO4.

[0107] 4. Application examples of powder cores

[0108] The above-mentioned powder magnetic core 1 is preferably used for electronic components. Examples of the electronic components include inductors, choke coils, noise filters, reactors, transformers, etc. The electronic component includes, for example, the powder magnetic core 1 and a coil.

[0109] Figure 4-Figure 6The inductors 10 , 20 , and 30 shown are an example of the electronic component of the present disclosure. Figure 4 The inductor 10 shown includes a powder magnetic core 11 and a coil 13 . Figure 5 The inductor 20 shown includes a powder magnetic core 21 and a coil 23 . Figure 6 The inductor 30 shown includes a powder magnetic core 31 and a coil 33. The powder magnetic cores 11, 21, and 31 have the same structure as the powder magnetic core 1.

[0110] Figure 7 The noise filter 40 shown is an example of the electronic component of the present disclosure. The noise filter 40 includes a powder magnetic core 41 and a pair of coils 43 and 45. The powder magnetic core 41 has the same structure as the powder magnetic core 1.

[0111] Figure 8 The reactor 50 shown is an example of the electronic component of the present disclosure. The reactor 50 includes a powder magnetic core 51 and a coil 53. The powder magnetic core 51 has the same structure as the powder magnetic core 1.

[0112] Fig. 9 The transformer 60 shown is an example of the electronic component of the present disclosure. The transformer 60 includes a powder magnetic core 61 and a pair of coils 63 and 65. The powder magnetic core 61 has the same structure as the powder magnetic core 1 described above.

[0113] The powder magnetic core 1 is preferably used in an electronic device. The electronic device includes an electronic component. Examples of the electronic component include the above-mentioned electronic components.

[0114] Fig.10 The noise filter 70 shown is an example of an electronic device of the present disclosure. The noise filter 70 includes an element 71 and capacitors 73, 75, and 77. The element 71 is an example of an "electronic element" of the present disclosure. The element 71 is, for example, Figure 7 The noise filter 40 shown has the same structural components.

[0115] The powder magnetic core 1 is preferably used in an electric motor. Examples of the electric motor include a motor and a linear motion actuator.

[0116] Fig.11 The motor 80 shown is an example of the electric motor of the present disclosure. The motor 80 includes a rotor 80A and a stator 80B. The stator 80B includes a powder magnetic core 81 and a coil 83. The powder magnetic core 81 has the same structure as the powder magnetic core 1 described above.

[0117] Fig.12The generator 90 shown is an example of the generator of the present disclosure. The generator 90 includes a rotor 90A and a stator 90B. The stator 90B includes a powder magnetic core 91 and a coil 93. The powder magnetic core 91 has the same structure as the powder magnetic core 1 described above.

[0118] Example

[0119] Hereinafter, the present invention will be described in more detail by way of examples.

[0120] 1. Production of pressed powder core

[0121] Table 1 shows the compositions of the alloy particles of the powder magnetic cores of Examples 1 to 3 and Comparative Examples 1 and 2. The description "Fe-6.5%Si" in the "Core Composition" column of Table 1 means that the core of the alloy particle contains 6.5 mass% silicon, and the balance is iron and inevitable impurities.

[0122] [Table 1]

[0123]

[0124] Table 2 shows the composition of the alloy particles of the powder magnetic cores of Examples 4 and 5 and Comparative Examples 3 and 4. The description "Fe-6.5% Si" in the "Core Composition" column of Table 2 means that the core of the alloy particle contains 6.5% by mass of silicon, and the balance is iron and inevitable impurities. The description "Fe-1.0% Si" in the "Core Composition" column of Table 2 means that the core of the alloy particle contains 1.0% by mass of silicon, and the balance is iron and inevitable impurities.

[0125] [Table 2]

[0126]

[0127] (1) Examples 1 to 3

[0128] In Examples 1 to 3, a core containing 6.5 mass % of silicon and the balance being iron and inevitable impurities was used for the raw material powder, and the core was coated with MnZn ferrite by a plating method.

[0129] In Example 1, after covering the core, press molding was performed at 1 GPa, and annealing was performed by holding at 800° C. for 1.5 hours. During the cooling process, cooling was performed from 600° C. to 300° C. at a cooling rate of 2° C. / min.

[0130] In Example 2, after covering the core, press molding was performed at 1 GPa, and annealing was performed by holding at 1000° C. for 1.5 hours. During the cooling process, cooling was performed from 600° C. to 300° C. at a cooling rate of 2° C. / min.

[0131] In Example 3, after covering the core, the powder was kept at 900°C for 1.5 hours, heat treated, and cooled. During the cooling process, it was cooled from 600°C to 300°C at a cooling rate of 2°C / min. Then, it was press-formed at 1 GPa, kept at 1000°C for 1.5 hours, annealed, and cooled. During the cooling process, it was cooled from 600°C to 300°C at a cooling rate of 2°C / min.

[0132] (2) Comparative Examples 1 and 2

[0133] Comparative Examples 1 and 2 were similar to Examples 1 to 3, except that a core containing 6.5 mass % of silicon and the balance being iron and inevitable impurities was used as a raw material powder, and the core was coated with MnZn ferrite by a plating method.

[0134] In Comparative Example 1, after covering the core, press molding was performed at 1 GPa, and annealing was performed by holding at 600° C. for 0.5 hours. During the cooling process, cooling was performed from 600° C. to 300° C. at a cooling rate of 1° C. / min.

[0135] In Comparative Example 2, after covering the core, press molding was performed at 1 GPa, and annealing was performed by holding at 600° C. for 1.5 hours. During the cooling process, cooling was performed from 600° C. to 300° C. at a cooling rate of 1° C. / min.

[0136] (3) Embodiments 4 and 5

[0137] In Examples 4 and 5, a core containing 6.5 mass % of silicon and the balance being iron and inevitable impurities was used for the raw material powder, and the core was coated with Mg ferrite by a plating method.

[0138] In Example 4, after covering the core, press molding was performed at 1 GPa, and annealing was performed by holding at 1050° C. for 2.0 hours. During the cooling process, cooling was performed from 600° C. to 300° C. at a cooling rate of 2° C. / min.

[0139] In Example 5, after covering the core, the powder was kept at 900°C for 1.5 hours and heat treated and cooled. During the cooling process, it was cooled from 600°C to 300°C at a cooling rate of 2°C / min. Then, it was press-formed at 1 GPa, kept at 1050°C for 2.0 hours, annealed and cooled. During the cooling process, it was cooled from 600°C to 300°C at a cooling rate of 2°C / min.

[0140] (4) Comparative Examples 3 and 4

[0141] In Comparative Example 3, a core containing 1.0 mass% silicon and the balance being iron and inevitable impurities was used for the raw material powder, and the core was coated with Mg ferrite by a plating method. After coating the core, press molding was performed at 1 GPa, and annealing was performed while being maintained at 1050°C for 2.0 hours. During the cooling process, cooling was performed from 600°C to 300°C at a cooling rate of 2°C / min.

[0142] In Comparative Example 4, a core containing 1.0 mass% silicon and the balance being iron and inevitable impurities was used for the raw material powder, and the core was coated with MnZn ferrite by a plating method. After coating the core, press molding was performed at 1 GPa, and annealing was performed while being maintained at 1050°C for 1.5 hours. During the cooling process, cooling was performed from 600°C to 300°C at a cooling rate of 2°C / min.

[0143] It should be noted that in the above-mentioned Examples and Comparative Examples, when the core is covered with MnZn ferrite by plating, the ratio (molar ratio) of the divalent ion concentration contained in the aqueous solution used for the plating method is Fe: 2+ :Mn 2+ :Zn 2+ =100:8:12.

[0144] In the above-mentioned examples and comparative examples, when the core is coated with Mg ferrite by plating, the ratio (molar ratio) of the divalent ion concentration contained in the aqueous solution used for the plating method is Fe: 2+ :Mg 2+ =100:100.

[0145] 2. Evaluation method of the crystal phase of the cover

[0146] The crystal phase of the coating was identified by XRD (X-ray diffraction) analysis of the cross section of the powder core. In Examples 4 and 5 and Comparative Example 3, the cross section of the powder core was observed using SEM, and Mg was detected from the coating by EDS analysis.

[0147] 3. Evaluation method of metal particle morphology

[0148] An arbitrary cross section of the powder magnetic core is observed using a SEM to check whether a plurality of metal particles are dispersed between adjacent alloy particles in a manner sandwiched by the covering portion. Specifically, it is checked whether two or more metal particles are arranged in a spaced manner between adjacent alloy particles.

[0149] 4. Evaluation method of eddy current loss

[0150] The eddy current loss of the powder magnetic core was evaluated using a measuring device (BH Analyzer, Iwasaki Communication Co., Ltd., Model SY-8218). The evaluation was performed under the conditions of 0.1 T and 10 kHz using the following modified Steinmetz equation regarding iron loss.

[0151] [Mathematical formula 1]

[0152]

[0153] P CV : Iron loss

[0154] Hysteresis loss term

[0155] K C (B m f) 2 : Eddy current loss term

[0156] K e (B m f) 1.5 : Residual loss term

[0157] 5. Strength evaluation method

[0158] A test piece (50 mm×4 mm×3 mm thick) of the powder core was prepared and subjected to a three-point bending test to obtain an index of strength.

[0159] 6. Evaluation method of relative magnetic permeability

[0160] The relative magnetic permeability of the powder magnetic core was measured using a measuring device (BH Analyzer, Iwasaki Communication Co., Ltd., Model SY-8218). The relative magnetic permeability was evaluated under the conditions of 0.1 T and 10 kHz.

[0161] 7. Evaluation results

[0162] The evaluation results are shown in Tables 1 and 2.

[0163] Examples 1 to 3 satisfy the following conditions (A) to (C).

[0164] Condition (A): The core portion of the alloy particle is covered with a coating portion containing Fe2SiO4.

[0165] Condition (B): A plurality of metal particles are dispersedly arranged on the outer peripheral edge of the coating portion, and the metal particles contain silicon at a lower ratio than that of the alloy.

[0166] Condition (C): At least a portion of the metal particles is present between adjacent alloy particles in a state of being sandwiched by the covering portion.

[0167] In contrast, Comparative Examples 1 and 2 do not satisfy the above conditions (A) to (C). In Comparative Example 1, spinel Fe3O4 was observed as the crystal phase of the coating, and no metal particles were observed. In Comparative Example 2, the metal particles were connected rather than dispersed.

[0168] In Examples 1 to 3 satisfying the above conditions (A) to (C), the eddy current loss is 1.8 kW / m 3 , 1.9kW / m 3 , 1.8kW / m 3 In Comparative Examples 1 and 2 that do not satisfy the above conditions (A) to (C), the eddy current losses are 9.3 kW / m 3 、7.8kW / m 3 . In Examples 1 to 3, since the covering portion of the alloy particles contains Fe2SiO4 instead of iron oxide, it can be considered that the insulation between the alloy particles is high and the eddy current loss can be suppressed. In addition, in Examples 1 to 3, a plurality of metal particles are dispersed between adjacent alloy particles in the form of being sandwiched by the covering portion, so it can be considered that it is not easy to become a path for eddy current and the eddy current loss can be suppressed. On the other hand, in Comparative Example 1, the annealing temperature is relatively low, at 600°C, and the annealing time is relatively short, at 0.5 hours, so it can be considered that the formation reaction of Fe2SiO4 is difficult to accelerate and the eddy current loss becomes larger. In Comparative Example 2, during the cooling process, the cooling rate from 600°C to 300°C is relatively slow, at 1°C / min, so it can be considered that when a trace amount of FeO is dissolved in Fe2SiO4, the eddy current loss becomes larger due to the eutectic phase transformation of FeO.

[0169] In Examples 1 to 3 that satisfy the above conditions (A) to (C), the strength index of the three-point bending test is 58 MPa to 80 MPa. In Comparative Examples 1 and 2 that do not satisfy the above conditions (A) to (C), the strength index of the three-point bending test is 35 MPa and 61 MPa, respectively. In Examples 1 to 3, since the silicon concentration of the metal particles is low, deformation will occur during press molding, and the alloy particles are easily combined with each other, so the strength is improved. In addition, in Examples 1 to 3 and Comparative Example 2, since the covering portion of the alloy particles contains Fe2SiO4 whose melting point is lower than the melting point of iron oxide, it can be considered that the covering portions are easily sintered to each other, and the strength is improved.

[0170] In Examples 1 to 3 satisfying the above conditions (A) to (C), the relative magnetic permeability is 62 to 80. In Comparative Examples 1 and 2 not satisfying the above conditions (A) to (C), the relative magnetic permeabilities are 40 and 65, respectively. In Examples 1 to 3, a plurality of metal particles are dispersed between adjacent alloy particles in the form of being sandwiched by the covering portion, and the alloy particles are magnetically connected to each other, thereby improving the relative magnetic permeability.

[0171] Examples 4 and 5 satisfy the following conditions (D) to (F).

[0172] Condition (D): The core portion of the alloy particle is covered with a coating portion containing a solid solution of Fe2SiO4 and Mg2SiO4.

[0173] Condition (E): A plurality of metal particles are disposed in a dispersed manner on the outer peripheral edge of the coating portion, and the metal particles contain silicon at a lower ratio than that of the alloy.

[0174] Condition (F): At least a portion of the metal particles is present between adjacent alloy particles in a state of being sandwiched by the covering portion.

[0175] In contrast, Comparative Examples 3 and 4 do not satisfy the above conditions (D) to (F). In Comparative Example 3, MgFeSiO4 was observed as the crystal phase of the covering portion, but the metal particles were connected rather than dispersed. In Comparative Example 4, Fe2SiO4 was observed as the crystal phase of the covering portion, but the metal particles were connected rather than dispersed.

[0176] In Examples 4 and 5 satisfying the above conditions (D) to (F), the eddy current losses are 1.8 kW / m 3 , 1.9kW / m 3 In Comparative Examples 3 and 4 which do not satisfy the above conditions (D) to (F), the eddy current losses are 350 kW / m 3 、450kW / m 3 . In Examples 4 and 5, the covering portion of the alloy particles contains a solid solution of Fe2SiO4 and Mg2SiO4 instead of iron oxide, so it can be considered that the insulation between the alloy particles is high, and the eddy current loss can be suppressed. In addition, in Examples 4 and 5, a plurality of metal particles are dispersed between adjacent alloy particles in the form of being clamped by the covering portion, so it can be considered that the metal particles are not easy to become the path of eddy current, and the eddy current loss can be suppressed. On the other hand, in Comparative Examples 3 and 4, the Si content in the core is lower than that in Examples 4 and 5, and it can be inferred that during the annealing process, an A3 phase transformation from the α phase to the γ phase occurred in the alloy contained in the core. Therefore, it can be considered that tiny cracks are generated in the covering portion, and sintering is caused between adjacent alloy particles through the cracks, the insulation is reduced, and the eddy current loss becomes larger.

[0177] In Examples 4 and 5 that satisfy the above conditions (D) to (F), the strength indexes of the three-point bending test are 74 MPa and 85 MPa, respectively. In Examples 4 and 5, high strengths equivalent to those of Examples 1 to 3 were obtained. In Examples 4 and 5, since the metal particles have a low silicon concentration, they deform during press molding, and the alloy particles are easily bonded to each other, so it can be considered that the strength is improved. In addition, in Examples 4 and 5, since the coating of the alloy particles contains a solid solution of Fe2SiO4 and Mg2SiO4 whose melting point is lower than the melting point of iron oxide, it can be considered that the coatings are easily sintered to each other, and the strength is improved.

[0178] In Examples 4 and 5 satisfying the above conditions (D) to (F), the relative magnetic permeabilities were 57 and 61, respectively. In Examples 4 and 5, the relative magnetic permeabilities were equal to those of Examples 1 to 3. In Examples 4 and 5, a plurality of metal particles were dispersed between adjacent alloy particles in the form of being sandwiched by the covering portion, and the alloy particles were magnetically connected to each other, thereby improving the relative magnetic permeability.

[0179] 8. Effects of the Embodiments

[0180] The powder magnetic core of this embodiment has small eddy current loss, high strength and high relative magnetic permeability.

[0181] The present invention is not limited to the above-described detailed embodiments, and various changes or modifications may be made within the scope of the claims of the present invention.

[0182] Industrial Applicability

[0183] The powder magnetic core of the present invention is particularly preferably used in applications such as motors, transformers, reactors, inductors, and noise filters.

[0184] Description of Reference Numerals

[0185] 1, 11, 21, 31, 41, 51, 61, 81, 91… pressed powder core

[0186] 3. 3A, 3B, 3C, 3D… alloy particles

[0187] 5…Core

[0188] 7… Covering

[0189] 9, 9A~9E…Metal particles

[0190] 10, 20, 30...Inductor (electronic component)

[0191] 13, 23, 33, 43, 45, 53, 63, 65, 83, 93… coils

[0192] 40…Noise filter (electronic components)

[0193] 50… Reactor (electronic component)

[0194] 60...Transformer (electronic component)

[0195] 70…Noise filter (electronic equipment)

[0196] 80…Motor (electric motor)

[0197] 90…Generator

[0198] L…Outline

[0199] L1…Part 1

[0200] L2…Part 2

Claims

1. A powder magnetic core comprising a plurality of alloy particles, The alloy particles have: a core formed of an alloy comprising iron and silicon; and a covering portion covering the core portion, The covering portion contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4, A plurality of metal particles are disposed in a dispersed manner on the outer periphery of the covering portion, wherein the metal particles contain silicon at a lower ratio than the alloy. At least a portion of the metal particles is present between adjacent alloy particles in a form of being sandwiched by the covering portion.

2. An alloy particle, comprising: a core formed of an alloy comprising iron and silicon; and a covering portion covering the core portion, The covering portion contains Fe2SiO4 or a solid solution of Fe2SiO4 and Mg2SiO4, A plurality of metal particles are disposed in a dispersed manner on the outer periphery of the coating portion, and the metal particles contain silicon at a lower ratio than that of the alloy.

3. The powder magnetic core according to claim 1, wherein: The covering portion contains a solid solution of Fe2SiO4 and Mg2SiO4, The solid solution has an olivine structure.

4. The powder magnetic core according to claim 1 or claim 3, wherein: The core has the following composition composition: Contains by mass% Silicon (Si): 2% or more and 10% or less, Aluminum (Al): 0% or more and 10% or less, Chromium (Cr): 0% to 20% inclusive, with the remainder being iron and inevitable impurities.

5. The powder magnetic core according to claim 4, wherein: The component composition is a composition that does not cause an A3 phase transition from an α phase to a γ phase at a temperature of 800° C. to 1200° C.

6. The alloy particles according to claim 2, wherein The covering portion contains a solid solution of Fe2SiO4 and Mg2SiO4, The solid solution has an olivine-type structure.

7. The alloy particles according to claim 2 or claim 6, wherein: The core has the following composition composition: Contains by mass% Silicon (Si): 2% or more and 10% or less, Aluminum (Al): 0% or more and 10% or less, Chromium (Cr): 0% to 20% inclusive, with the remainder being iron and inevitable impurities.

8. The alloy particles according to claim 7, wherein The component composition is a composition that does not cause an A3 phase transition from an α phase to a γ phase at a temperature of 800° C. to 1200° C. 9 . An electronic component comprising the powder magnetic core according to claim 1 or claim 3 . 10 . The electronic component according to claim 9 , comprising the powder magnetic core and a coil. 11 . An electronic device comprising the electronic component according to claim 9 . 12 . An electric motor comprising the powder magnetic core according to claim 1 or claim 3 . 13 . A generator comprising the powder magnetic core according to claim 1 or claim 3 .

Citation Information

Patent Citations

  • Soft magnetic material and method for manufacturing the same

    JP2014060183A

  • Method for manufacturing soft magnetic material

    JP2016086124A

  • Magnetic material, electronic component, and manufacturing method of magnetic material

    JP2019009307A

  • Powder magnetic core, powder for magnetic core and method for manufacturing the same

    JP2019075566A